Preparation method and application of polypyrrole and its derived carbon-coated ferrous fluoride

By coating polypyrrole and its derived carbon layer on the surface of ferrous fluoride, the problems of poor conductivity and insufficient cycle stability of the positive electrode material of lithium-ion batteries are solved, and battery performance with high capacity and long cycle life is achieved.

CN118782759BActive Publication Date: 2025-03-04CHONGQING TECH & BUSINESS UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410734298.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-03-04
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials such as LiFePO4 and transition metal layered oxides limit their application in high-capacity and long-cycle life lithium-ion batteries due to problems such as low theoretical specific capacity, toxic elements, and high cost.

Method used

By establishing polypyrrole and its derived carbon-coated shell on the surface of ferrous fluoride, the conductivity is improved, the side reaction between the positive electrode material and the electrolyte is suppressed, and the threshold volume changes are limited, thereby improving electrochemical performance.

Benefits of technology

The stable release of high capacity is achieved, and the cycle stability and electrochemical performance of the battery are improved, so that the lithium-ion battery can still maintain a higher battery capacity after longer cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118782759B_ABST
    Figure CN118782759B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of polypyrrole and its derived carbon coated ferrous fluoride, and relates to the technical field of lithium ion battery preparation. The present invention improves the overall electrochemical performance of the composite material by regulating the coating temperature and time to control the coating thickness of the conductive polymer and its derived carbon. Compared with the prior art, the FeF2 composite material coated with the conductive polymer and the derived carbon is prepared by a safer liquid phase reaction to synthesize the precursor and a simple and easy-to-operate low-temperature vapor deposition technology. The prepared polypyrrole coating layer and the derived carbon layer can improve the conductivity of ferrous fluoride, inhibit the interface side reaction, and limit the threshold volume change to improve the cycle stability of ferrous fluoride, so that the prepared composite material still maintains a capacity of 182.1 mAh·g after 100 cycles in a 0.1C current density ester electrolyte. ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery preparation, in particular to a preparation method and application of polypyrrole and its derived carbon-coated ferrous fluoride. Background Art

[0002] Lithium-ion batteries (LIBs) have been widely used in human daily life. With the growing demand for energy density in portable electronic devices and electric vehicles, the intercalation materials (LiFePO4 and transition metal layered oxide cathodes) currently used in commercial lithium-ion battery cathodes are limited in their further application in the new generation of high-capacity, long-cycle-life lithium-ion batteries due to their low theoretical specific capacity, toxic and harmful elements such as Co and Ni, low reserves, and high costs. Therefore, it is urgent to develop new commercial cathode materials.

[0003] Compared with traditional intercalation cathode materials, conversion cathode materials have attracted widespread attention due to their ability to undergo multi-electron reactions, high theoretical specific capacity, low price, and environmental friendliness. Typical conversion cathodes mainly include sulfide elements and their compounds, metal halides, etc., among which metal halides are further divided into metal fluorides and metal chlorides. After comprehensively considering conditions such as element abundance and specific capacity, iron, due to its high abundance and low cost, makes iron-based conversion cathode materials promising for large-scale manufacturing of any battery. Iron-based fluorides are divided into FeF2 and FeF3, with theoretical specific capacities of 571 mAh g and 1.3 mAh g, respectively. -1 and 712mAh g -1 , which is much higher than commercial intercalation cathode materials (e.g. LiCoO2 274 mAh g -1 、LiFePO4170mAh g -1 ). Although FeF3 has a higher theoretical specific capacity than FeF2, it also has a more complicated lithiation / delithiation process. At the same time, due to the strong electronegativity of the F element, its intrinsic conductivity is poor, volume expansion and irreversible phase transformation during the cycle, and the liquid-solid reaction interface between FeF2 and the organic electrolyte is unstable (many side reactions). As the number of charge and discharge cycles increases, the organic electrolyte continues to decompose, causing serious dissolution of active materials and irreversible formation of the positive electrode solid electrolyte layer (CEI), which in turn hinders the transmission of lithium ions, which limits its practical application.

[0004] Referring to CN115411253A, a method for preparing a carbon-coated one-dimensional ferrous fluoride positive electrode material is disclosed. The preparation method utilizes liquid phase reaction to synthesize precursors, electrospinning composite and high temperature solid phase reaction techniques to embed transition metal fluorides into conjugated polymers, and utilizes the nano properties, conductivity and structural toughness of one-dimensional carbon materials to improve the electrochemical activity, intrinsic conductivity and structural stability of metal fluorides, thereby comprehensively improving the electrochemical properties of metal fluorides.

[0005] Referring to CN116487544A, a method for preparing coral-like carbon-coated ferrous fluoride is disclosed. The method synthesizes trace oxygen-doped carbon-coated coral-like nano-ferrous fluoride (FeF2@C) in situ in one step through a simple sealed solid-phase calcination method, and effectively enhances the electrochemical performance of the electrode by achieving a balance between the nanoparticle size and structural stability of the iron-based fluoride conversion material.

[0006] CN112103479A discloses a method of using carbon nanotubes as a conductive network, wherein a lithiated perfluorosulfonic acid polymer is coated on the surface of ferrous fluoride to protect the loss of metal ions, thereby improving the cycle stability of the positive electrode material.

[0007] The above-mentioned existing technologies adopt improvement measures such as morphology control, element doping and composite carbon materials to solve the problems of poor conductivity, voltage hysteresis, volume expansion and poor electrolyte compatibility of ferrous fluoride. However, these methods have shortcomings such as complex process, high cost and environmental pollution.

[0008] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a preparation method and application of polypyrrole and its derived carbon-coated ferrous fluoride, by establishing a polypyrrole (PPy) and its derived carbon-coated shell layer on the surface of ferrous fluoride to improve its conductivity, inhibit the side reaction between the positive electrode material and the electrolyte to reduce the formation of the irreversible CEI layer, limit the volume change during the cycle, so as to solve the problems raised in the background technology.

[0010] To achieve the above object, the present invention provides the following technical solution: a method for preparing polypyrrole and its derivative carbon-coated ferrous fluoride, comprising at least the following steps:

[0011] S1: Mix the reduced iron powder and the fluorosilicic acid aqueous solution and place at room temperature for 24 hours, centrifuge to separate the light green supernatant to remove the excess iron powder precipitation, and vacuum dry to obtain FeSiF6·6H2O (ferrous hexafluorosilicate hexahydrate) crystal powder;

[0012] S2: calcining FeSiF6·6H2O crystal powder in a tube furnace and then annealing under argon flow to obtain FeF2 (ferrous fluoride) powder material;

[0013] S3: A certain amount of FeF2 powder is sealed in a container bottle containing pyrrole monomer, where the pyrrole monomer solution is at the bottom of the bottle, and the FeF2 powder is placed on filter paper and suspended in the air, and then placed in a vacuum oven to obtain a FeF2@PPy composite material;

[0014] S4: The FeF2@PPy composite material is annealed in a tubular furnace under an argon flow to finally obtain a FeF2@C carbon-coated ferrous fluoride composite material.

[0015] Preferably, the iron powder in S1 is 2 g, the fluorosilicic acid is 10 g, and the vacuum drying temperature is 60°C;

[0016] The chemical reaction formula between the iron powder and the hydrofluorosilicic acid aqueous solution in S1 is:

[0017] Fe(g)+H2SiF6(l)→FeSiF6·6H2O(l)+H2(g).

[0018] Preferably, the FeSiF6·6H2O crystal powder in S2 first removes bound water during calcination, and then decomposes to generate SiF4 gas and FeF2, and the reaction formula is:

[0019] FeSiF6·6H2O(s)→FeF2(s)+SiF4(g)

[0020] The heating rate during the calcination is 5°C / min.

[0021] Preferably, the annealing temperature in S2 is 260° C. and the duration is 4 hours.

[0022] Preferably, the temperature at which S3 is placed in the vacuum oven is 40° C. and the standing time is 10 min.

[0023] Preferably, the annealing temperature in S4 is 350°C.

[0024] An application of polypyrrole and its derived carbon-coated ferrous fluoride, comprising at least the following steps:

[0025] Step 1: Use FeF2@PPy composite material as battery positive electrode material;

[0026] Step 2: dissolving the positive electrode material, conductive carbon black and binder (PVDF) in an organic solvent (NMP) in a ratio of 8:1:1 and stirring to prepare a slurry;

[0027] Step 3: The slurry in step 2 is evenly coated on the aluminum current collector and vacuum dried for 10 hours, and the cut pieces are weighed to obtain the corresponding positive electrode material electrode sheets.

[0028] Preferably, the positive electrode material electrode sheet is used to assemble a lithium battery.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention improves the overall electrochemical performance of the composite material by controlling the coating thickness of the conductive polymer and its derived carbon through the coating temperature and time. Compared with the prior art, the precursor is synthesized by a safer liquid phase reaction, and the conductive polymer and carbon material are coated on the FeF2 surface by a simple and easy-to-operate low-temperature vapor deposition technology, thereby utilizing the conductive polymer PPy and carbon to improve the conductivity, stabilize the electrochemical reaction interface, and limit the threshold volume change, thereby obtaining a high-capacity stable release;

[0031] 2. The present invention provides a method for preparing polypyrrole and its derivative carbon-coated ferrous fluoride, which is simple and easy to operate and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 X-ray diffraction (XRD) diagram of the polypyrrole-coated ferrous fluoride composite material prepared in Comparative Examples 1 and 2;

[0034] Figure 2 XRD diagram of the polypyrrole-coated ferrous fluoride composite material prepared in Comparative Examples 3 and 4;

[0035] Figure 3 The Fe-attached 3+ XRD patterns of FeF2 powder material and suspended prepared polypyrrole coated ferrous fluoride composite material;

[0036] Figure 4 XRD diagram of the polypyrrole-coated ferrous fluoride composite material prepared in Examples 1 to 3;

[0037] Figure 5 XRD diagram of the polypyrrole-coated ferrous fluoride composite material prepared in Examples 3 to 5;

[0038] Figure 6The SEM images of the material prepared in step (2) of Example 1 and the material prepared in Example 5, wherein (a) is a SEM image of FeF2 at a magnification of 100k, and (b) is a SEM image of Example 5 at a magnification of 100k;

[0039] Figure 7 This is the full element XPS graph corresponding to the polypyrrole-coated ferrous fluoride composite material prepared in Example 5;

[0040] Figure 8 The XPS graphs corresponding to the polypyrrole-coated ferrous fluoride composite material prepared in Example 5, wherein (a) is the XPS graph of C1s, (b) is the XPS graph of N1s, (c) is the XPS graph of Fe 2p, and (d) is the XPS graph of F1s;

[0041] Fig. 9 A comparison diagram of the AC impedance of the lithium-ion batteries prepared in Examples 3 to 5 and step (2) of Example 1;

[0042] Fig.10 The cyclic voltammetry comparison diagrams of the lithium ion batteries prepared in Examples 3 to 5 at different cycle times are shown in Figure 5, where (a) is the cyclic voltammetry comparison diagram of Example 5 at 0.3 mV s -1 (b) is the CV curve of Example 4 at 0.3 mV s -1 CV curves at 0.3 mV s -1 The CV curve below;

[0043] Fig.11 A comparison chart of the cycle performance of the lithium-ion batteries prepared in Examples 3 to 5 and step (2) of Example 1 at a rate of 0.1C;

[0044] Fig.12 A comparison chart of the rate performance of the lithium-ion batteries prepared in Examples 3 to 5 at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 0.1C rates;

[0045] Fig.13 XRD diagram of the carbon-coated ferrous fluoride composite material prepared in Example 6 and Comparative Examples 6-7;

[0046] Fig.14 is a transmission electron microscope (TEM) image of the composite material of Example 6;

[0047] Fig.15 Comparison diagram of the AC impedance of the lithium-ion batteries prepared in Examples 4 and 6 and step (2) of Example 1;

[0048] Fig.16 A comparison chart of the cycle performance of lithium-ion batteries prepared in Examples 4, 6 and Comparative Example 7 at a rate of 0.1C; DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0050] Embodiment 1:

[0051] A method for preparing polypyrrole and its derivative carbon-coated ferrous fluoride, comprising at least the following steps:

[0052] S1: Mix the reduced iron powder and the fluorosilicic acid aqueous solution and place at room temperature for 24 hours, centrifuge to separate the light green supernatant to remove the excess iron powder precipitation, and vacuum dry to obtain FeSiF6·6H2O (ferrous hexafluorosilicate) crystal powder;

[0053] S2: calcining FeSiF6·6H2O crystal powder in a tube furnace and then annealing under argon flow to obtain FeF2 (ferrous fluoride) powder material;

[0054] S3: A certain amount of FeF2 powder is sealed in a container bottle containing pyrrole monomer, where the pyrrole monomer solution is at the bottom of the bottle, and the FeF2 powder is placed on filter paper and suspended in the air, and then placed in a vacuum oven to obtain a FeF2@PPy composite material;

[0055] The iron powder in S1 is 2 g, the fluorosilicic acid is 10 g, and the vacuum drying temperature is 60°C;

[0056] The chemical reaction formula between the iron powder and the hydrofluorosilicic acid aqueous solution in S1 is:

[0057] Fe(g)+H2SiF6(l)→FeSiF6·6H2O(l)+H2(g).

[0058] The FeSiF6·6H2O crystal powder in S2 first removes bound water during calcination, and then decomposes to generate SiF4 gas and FeF2. The reaction formula is:

[0059] FeSiF6·6H2O(s)→FeF2(s)+SiF4(g)

[0060] The heating rate during calcination was 5°C / min.

[0061] The annealing temperature in S2 is 150°C to 300°C, and the duration is 2h to 4h.

[0062] The temperature of S3 placed in the vacuum oven is 40-60° C. and the standing time is 10 min-30 min.

[0063] The annealing temperature in S4 is 300°C to 500°C.

[0064] An application of polypyrrole and its derived carbon-coated ferrous fluoride, comprising at least the following steps:

[0065] Step 1: Use FeF2@PPy composite material as battery positive electrode material;

[0066] Step 2: dissolving the positive electrode material, conductive carbon black and binder (PVDF) in an organic solvent (NMP) in a ratio of 8:1:1 and stirring to prepare a slurry;

[0067] Step 3: The slurry in step 2 is evenly coated on the aluminum current collector and vacuum dried for 10 hours, and the cut pieces are weighed to obtain the corresponding positive electrode material electrode sheets.

[0068] Positive electrode material electrode sheets are used to assemble lithium batteries.

[0069] The lithium battery is assembled as follows. In this embodiment, it is a CR2032 button-type half-cell:

[0070] Assemble CR2032 button half-cells in an argon glove box (water <0.01 ppm, oxygen <0.01 ppm), wherein the positive electrode is the electrode sheet prepared in step 3 above, the counter electrode is a lithium sheet, the diaphragm is Celgard 2500, and the electrolyte is 1 mol / LLiPF6 / FEC:EMC (volume ratio 3:7) electrolyte on the diaphragm. After assembly, seal with a tablet press.

[0071] Embodiment 2:

[0072] Example 2 is the same as Example 1, except that the material is placed in a vacuum oven at 50° C. for 30 minutes.

[0073] Embodiment 3:

[0074] Example 3 is the same as Example 1, except that the material is placed in a vacuum oven at 40° C. for 30 minutes.

[0075] Embodiment 4:

[0076] Example 4 is the same as Example 1, except that the material is placed in a vacuum oven at 40° C. for 20 min.

[0077] Embodiment 5:

[0078] Example 5 is the same as Example 1, except that the material is placed in a vacuum oven at 40° C. for 10 min.

[0079] Embodiment 6:

[0080] Example 6 is the same as Example 5, except that the polypyrrole-coated material is annealed at 350° C. for 4 h in an argon flow in a tube furnace to obtain a carbon-coated ferrous fluoride (FeF2@C) powder material.

[0081] Comparative Example 1:

[0082] 0.2 g FeF2 powder and 0.2 mL pyrrole monomer were added to 30 mL deionized water solution. The mixed solution was ultrasonically dispersed for 5 min and then magnetically stirred at a certain speed in an ice water bath. Then 0.15 mol / L FeCl3 solution was added to the above solution and allowed to stand for 5 h. The centrifuged product was washed several times and finally, the FeF2@PPy composite material was obtained by vacuum drying at 60 °C for 12 h.

[0083] Comparative Example 2:

[0084] Comparative Example 2 is the same as Comparative Example 1, except that the solvent is replaced by anhydrous ethanol from deionized water.

[0085] Comparative Example 3:

[0086] Comparative Example 3 is the same as Comparative Example 2, except that the oxidant is replaced by ammonium persulfate from FeCl3.

[0087] Comparative Example 4:

[0088] Comparative Example 4 is the same as Comparative Example 3, except that the FeF2@PPy composite material obtained by this method is calcined at 180°C for 2h.

[0089] Comparative Example 5:

[0090] The difference between Comparative Example 5 and Comparative Example 1 is that 0.2 g of FeF2 powder and 0.3 mol / L of FeCl3 solution are added to 30 mL of anhydrous ethanol solution, the mixed solution is ultrasonically dispersed for 5 min, and then magnetically stirred at a certain speed until the mixture is uniform, and then placed at 60 ° C. and vacuum dried for 12 h to obtain FeF2 powder. 3+ of FeF2 powder.

[0091] The polypyrrole suspension was coated with Fe using step (3) in Example 1. 3+ The FeF2 powder was finally used to obtain FeF2@PPy composite material.

[0092] Comparative Example 6:

[0093] Comparative Example 6 is the same as Example 6, except that the carbonization temperature is 300°C.

[0094] Comparative Example 7:

[0095] Comparative Example 7 is the same as Example 6, except that the carbonization temperature is 400°C.

[0096] Comparative Example 8:

[0097] Comparative Example 8 is the same as Example 6, except that the carbonization temperature is 450°C.

[0098] Performance Testing

[0099] 1. Comparison of XRD patterns of composite materials prepared in Comparative Examples 1 to 5

[0100] Comparative Examples 1 to 5 were subjected to X-ray diffraction characterization tests. The experimental results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that when the composite material is prepared by the traditional solvent method with FeCl3 as the oxidant, water as the solvent will cause most of the FeF2 to dissolve, while ethanol as the solvent will cause the FeF2 phase to change; when ammonium persulfate is used as the oxidant, the FeF2 phase still changes and a large amount of unreacted ammonium persulfate remains because ammonium persulfate is insoluble in ethanol. On this basis, the composite material in Comparative Example 3 is calcined at 180°C to remove excess ammonium persulfate, but Figure 2 The results show that after calcination, the XRD of the material in Comparative Example 4 has a mixed peak. Based on Comparative Examples 1 to 4, ethanol is used as a solvent to first load the Fe in the oxidant. 3+ , Figure 3 Display load Fe 3+ After that, the material phase has changed.

[0101] 2. Comparison of XRD patterns of composite materials of Examples 1 to 3 at different experimental temperatures

[0102] It can be seen from the XRD of Example 1 that this method has no effect on the physical phase of FeF2. However, it was observed during the experiment that too high a temperature would cause the pyrrole liquid to reflux and drip directly onto the surface of the FeF2 particles, causing serious agglomeration. Therefore, the XRD characterization test was performed again after lowering the temperature in Examples 2 and 3. Figure 4 It can be seen that the change in temperature has no effect on its physical phase. Combined with the experimental phenomena, 40°C was selected as the optimal experimental temperature.

[0103] 3. Characterization and performance comparison of composite materials of Examples 3 to 5 at different experimental times

[0104] from Figure 5 It can be seen from the local image that after the composite material is coated with trace amounts of polypyrrole, a broad amorphous peak appears at a diffraction angle of 15 to 30°; Figure 6 (b) Compared with (a), the particle size of the nanoparticles is significantly larger and the particles show a significant coating layer; XPS total spectrum ( Figure 7) and the XPS spectrum of C1s ( Figure 8 The peaks at 284.8 eV and 286.3 eV in (a) belong to CC and CN of polypyrrole-derived carbon and N1s in the XPS spectrum ( Figure 8 The strong peak at 400.2 eV in (b) belongs to pyrrolic nitrogen (-NH-), which proves the successful coating of polypyrrole in the composite material. In addition, the XPS spectrum of Fe 2p ( Figure 8 (c)) shows that Fe 2p is composed of two groups of peaks, corresponding to 2p 3 / 2 Orbitals and 2p 1 / 2 orbital, which is due to the spin-orbit coupling effect of the Fe element. 3 / 2 With Fe 2p 1 / 2 The main peaks are at 711.4 and 725.0 eV, respectively, with an energy difference of 13.6 eV. The area ratio of the two groups of peaks meets the requirement of 1:2. In addition, there are two satellite peaks at 717.6 and 732.0 eV in the spectrum. The XPS spectrum of F 1s ( Figure 8 (d)) Fe-F bond (685.2 eV) and Fe 2p 3 / 2 (711.4 eV) and Fe 2p 1 / 2 The (725.0 eV) peak proves the formation of FeF2 phase.

[0105] The lithium-ion batteries prepared in Examples 3 to 5 were placed in an electrochemical workstation CHI660e, with the low frequency set to 0.01 Hz, the high frequency set to 100,000 Hz, and the initial voltage set to the open circuit voltage. The AC impedance of the corresponding batteries was tested. The experimental results are shown in FIG. Fig. 9 As shown. Fig. 9 It can be seen that as the coating time shortens, the AC impedance of the corresponding battery continues to decrease. The decrease in AC impedance indicates that the conductivity of the battery is better, which is conducive to the improvement of the battery's cycle performance.

[0106] The lithium ion batteries prepared in Examples 3 to 5 were subjected to cyclic voltammetry tests using a chemical workstation CHI660e. The experimental results are as follows: Fig.10 As shown in (a), (b) and (c). Fig.10 It can be seen from (a), (b) and (c) that when the coating time is shortened, the thickness of the coating layer is more suitable. Among them, the redox peaks of the 3-cycle CV spectrum of the battery prepared in Example 5 have good overlap, indicating that it has good electrochemical stability.

[0107] The lithium ion batteries prepared in Examples 3 to 5 were tested for long cycle performance at a rate of 0.1C. The experimental results are as follows: Fig.11 As shown. Fig.11It can be seen that the coulombic efficiency of the battery under the coating experimental conditions of 40°C and 10 min is close to 100%, and its capacity remains at 182.1 mAh g after 100 cycles. -1 However, after 100 cycles, the battery capacity of the batteries of Examples 3 and 4 dropped to nearly zero, indicating that a suitable coating thickness in polypyrrole coating can make the battery have higher coulombic efficiency and battery capacity retention rate.

[0108] The lithium ion batteries prepared in Examples 3 to 5 were tested for rate performance at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C rates, respectively. The experimental results are as follows: Fig.12 As shown. Fig.12 It can be seen that the battery has the best rate performance under the coating experimental conditions of 40°C and 10 minutes.

[0109] 4. Comparison of XRD patterns of the composite materials of Example 6 and Comparative Examples 6 to 8 at different carbonization temperatures

[0110] from Fig.13 It can be seen that when the carbonization temperature reaches 400℃, iron oxides begin to appear in the FeF2@C composite material phase. As the carbonization temperature increases, the oxide content increases. Therefore, the optimal carbonization temperature is 350℃.

[0111] 5. Characterization and performance comparison of the composite materials of Example 6 and Comparative Example 7

[0112] from Fig.14 It can be seen from the TEM image that after the polypyrrole coating material is carbonized at 350°C, a uniform carbon coating layer is formed on the surface with a thickness of about 5-10nm.

[0113] The lithium-ion battery prepared in Example 6 was placed in an electrochemical workstation CHI660e, and the low frequency was set to 0.01 Hz, the high frequency was set to 100000 Hz, and the initial voltage was the open circuit voltage. The AC impedance of the corresponding battery was tested. The experimental results are as follows: Fig.15 As shown. Fig.15 It can be seen that the AC impedance of the battery decreases after carbonization. The decrease in AC impedance indicates that the carbon material improves the conductivity of the composite material.

[0114] The lithium ion batteries prepared in Example 6 and Comparative Examples 6 and 7 were tested for long cycle performance at a rate of 0.1C. The experimental results are as follows: Fig.16 As shown. Fig.16 It can be seen that when the temperature is too low, polypyrrole is not carbonized, and when the temperature is too high, there are too many oxides, both of which are not conducive to improving the electrochemical performance of the battery. This shows that the composite material with a carbonization temperature of 350°C has the best cycle performance in carbon coating.

[0115] The present invention can be known from the above embodiments that the coating thickness of the conductive polymer and its derived carbon is controlled by regulating the coating temperature and time to improve the overall electrochemical performance of the composite material. Compared with the prior art, a safer liquid phase reaction is used to synthesize the precursor, and a simple and easy-to-operate low-temperature vapor deposition technology is used to prepare the FeF2 composite material coated with the conductive polymer and the derived carbon. The prepared polypyrrole coating layer and the derived carbon layer can improve the conductivity of ferrous fluoride, inhibit the interface side reaction, and limit the threshold volume change, thereby improving the cycle stability of ferrous fluoride, so that the prepared composite material still maintains a capacity of 182.1 mAh·g after 100 cycles in a 0.1C current density ester electrolyte. -1 The scanning electron microscopy image of the polypyrrole-coated ferrous fluoride composite material is shown in the attached figure. Figure 6 As shown in (b), XRD characterization shows that the ferrous fluoride and polypyrrole composite material was successfully prepared.

[0116] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing polypyrrole and its derivative carbon-coated ferrous fluoride, characterized in that: At least the following steps are included: S1: Mix the reduced iron powder and the hydrofluorosilicic acid aqueous solution and react at room temperature for 24 hours, centrifuge to separate the light green supernatant to remove the excess iron powder precipitation, and vacuum dry to obtain FeSiF6·6H2O crystal powder; The iron powder in S1 is 2g, the fluorosilicic acid is 10g, and the vacuum drying temperature is 60°C S2: calcining FeSiF6·6H2O crystal powder in a tube furnace and then annealing under argon flow to obtain FeF2 powder material; The annealing temperature in S2 is 150°C to 300°C and the duration is 2h to 4h. S3: A certain amount of FeF2 powder is sealed in a container bottle containing pyrrole monomer, where the pyrrole monomer solution is at the bottom of the bottle, and the FeF2 powder is placed on filter paper and suspended in the air, and then placed in a vacuum oven to obtain a FeF2@PPy composite material; The temperature of the S3 placed in the vacuum oven is 40-60°C and the standing time is 10-30 minutes; S4: The FeF2@PPy composite material was annealed in an argon flow in a tube furnace to obtain a FeF2@C carbon-coated ferrous fluoride composite material. The annealing temperature in S4 is 300°C to 500°C.

2. An application of polypyrrole and its derivative carbon-coated ferrous fluoride in the preparation method of polypyrrole and its derivative carbon-coated ferrous fluoride according to claim 1, characterized in that: At least the following steps are included: Step 1: Use FeF2@PPy and FeF2@C composite materials as battery positive electrode materials respectively; Step 2: dissolving the positive electrode material, conductive carbon black and binder in an organic solvent in a ratio of 8:1:1 and stirring to prepare a slurry; Step 3: The slurry in step 2 is evenly coated on the aluminum current collector and vacuum dried for 4 to 10 hours, and the cut pieces are weighed to obtain the corresponding positive electrode material electrode sheets.

3. The use of polypyrrole and its derivative carbon-coated ferrous fluoride according to claim 2, characterized in that: The positive electrode material electrode sheet is used for assembling a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation and application of polymer-coated carbon nanotube / ferrous fluoride composite material

    CN112103479A

  • Carbon-coated one-dimensional ferrous fluoride positive electrode material as well as preparation method and application thereof

    CN115411253A

  • Coralline carbon coated ferrous fluoride as well as preparation method and application thereof

    CN116487544A

  • Polymer carbonized in-situ coated ferric fluoride composite positive electrode material and preparation method thereof

    CN106058222A

  • Preparation method of porous CoO@ nitrogen-doped carbon coaxial nanorod

    CN106654193A